2022
DOI: 10.1021/acs.chemmater.1c03563
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Alkali Metal Cation in the Early Stages of Crystallization of Halide Perovskites

Abstract: ABX3 metal halide perovskites revolutionized the research and development of new optoelectronics, including solar cells and light-emitting diodes. Processing polycrystalline thin films from precursor solutions is one of the core advantages of these materials since it enables versatile and cost-effective manufacturing. The perovskite film morphology, that is, continuous substrate coverage and low surface roughness, is of paramount importance for highly efficient solar cells and optoelectronic devices in general… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 63 publications
1
21
0
Order By: Relevance
“…19 Besides, it was reported that the organic ions in a conventional DMF or DMF/DMSO based perovskite precursor solution are not restricted inside the PbI 3 − inorganic framework, resulting in the emergence of an electrical double layer made of the respective counter ions surrounding the iodoplumbates and a diffuse layer. 126 Nevertheless, the single-crystal based perovskite precursor solution has been demonstrated to inherit the exceptional characteristics of the parent perovskite crystals, and fabricate the high-quality perovskite films with enhanced crystallinity, extended grain sizes, few grain boundaries and a low trap-state density. 118 For example, MA + ions are found to be captured inside the framework after the dissolution of MAPbI 3 single crystals in MA gas and form the viscous liquid; the perovskite structure retains to a certain extent even on diluting the viscous liquid in a weak coordination solvent, acetonitrile (ACN).…”
Section: Crystal Orientation Engineering Of Halide Perovskite Thin Filmsmentioning
confidence: 99%
“…19 Besides, it was reported that the organic ions in a conventional DMF or DMF/DMSO based perovskite precursor solution are not restricted inside the PbI 3 − inorganic framework, resulting in the emergence of an electrical double layer made of the respective counter ions surrounding the iodoplumbates and a diffuse layer. 126 Nevertheless, the single-crystal based perovskite precursor solution has been demonstrated to inherit the exceptional characteristics of the parent perovskite crystals, and fabricate the high-quality perovskite films with enhanced crystallinity, extended grain sizes, few grain boundaries and a low trap-state density. 118 For example, MA + ions are found to be captured inside the framework after the dissolution of MAPbI 3 single crystals in MA gas and form the viscous liquid; the perovskite structure retains to a certain extent even on diluting the viscous liquid in a weak coordination solvent, acetonitrile (ACN).…”
Section: Crystal Orientation Engineering Of Halide Perovskite Thin Filmsmentioning
confidence: 99%
“…As confirmed by previous works, the dissolution of the perovskite precursor salts into the solvents leads to the dynamic formation of different colloidal nanoparticles (NPs). 31 , 32 These colloidal NPs are the starting point for the nucleation and growth of perovskite grains during the spin coating process. Their chemical nature and stability are crucial for controlling the quality of the perovskite thin film.…”
mentioning
confidence: 99%
“…Nonclassical nucleation and growth mechanisms can explain these phenomena. 50 In addition, 207 Pb NMR measurements on the solution concentration series were performed to investigate the chemical environment of the Pb 2+ ion within the respective solutions. An upeld shi to lower ppm values is observed for increased solution concentration (Fig.…”
Section: Solution Characteristics and Chemistrymentioning
confidence: 99%